Characterization of Silica Particles and Concentration Dependent Adsorption Study of Biomolecules - Rahman, MA; Miah, MAJ; Ahmad, H (Bangladesh Journal of Scientific and Industrial Research, 2011)
Submicron-sized silica particles were initially characterized by scanning electron micrograph, FTIR spectroscopy and XRD analysis. The observations revealed that the highly dispersed amorphous silica particles were relatively monodispersed and the particles surface was covered with hydrogen bonded OH groups. Relatively higher magnitude of adsorption of cationic emulsifier and coagulation of silica particles suggested that particles were negatively charged. A comparative study of adsorption behavior of different biomolecules such as trypsin, albumin and lysozyme was also done at the respective isoelectric pH value. The magnitude of adsorption increased with the increase in the amount of immobilization per unit mass of silica particles. Key words: Silica; Amorphous; Adsorption behavior; Emulsifier; Biomolecules DOI: 10.3329/bjsir.v45i4.7377 Bangladesh J. Sci. Ind. Res. 45(4), 363-366, 2010